COSMOLOGICAL AND LEGAL ORDER IN DANTE’S «CONVIVIO» - Fonzo, Claudia Di; University of Florence (2015)
Dante’s convictions are examined in relation to the histories of jurisprudence and medieval philosophy and the article presents several original observations regarding the role of Moral Philosophy and the concept of the order as a legal and cosmological principle in Dante’s world. Some of these observations were partially addressed in the volume entitled Dante between jurisprudence, theology and ancient exegesis.